The effects of in vitro maturation duration on maturation rate and intracytoplasmic sperm injection-derived embryonic development in goats - Farizah, A.H.N.; Rahman, M.M.; Khadijah, W.E.W.; Abdullah, R.B. (Agricultural Research Communication Centre, 2015)
The aim of the present study was to evaluate the effects of in vitro maturation (IVM) duration on maturation rate and intracytoplasmic sperm. injection (ICSI)-derived embryonic development in goat embryos. Donor goats were superovulated following oestrus synchronisation prior to laparoscopic oocyte pick-up. The quality of oocytes was scored based on cumulus cell layers, which were graded A, B and C. The oocytes were cultured in IVM medium with two different IVM durations (18-21 h and 22-25 h) for the ICSI procedure. A total of 327 matured oocytes were used, of which 157 and 170 oocytes were used for 18-21 h and 22-25 h IVM duration, respectively. The embryo cleavage rate of Grade A from the 18-21 h IVM group was significantly (P<0.05) higher than that of grades B and C. However, in the 22-25 h IVM duration group, the cleavage rates for all grades of oocytes were not significantly (P>0.05) different. Regardless of oocyte grades, no significant differences in maturation rates and cleavage rates for all stages of embryonic development between the two groups of IVM durations were observed. The results suggest that both IVM durations have the same potential in ICSI-derived embryonic development.